Tourists' experience on destination loyalty: a case study of Islamic architecture in Kuala Terengganu. - Zulkifle, Nur Najwa; Saad, Mazni (2020)
A religious or spiritual attributes are emerging, such as Islamic tourism through several factors as a new tourism product in the tourism industry. Through several researches it can be seen that Islamic architecture has a potential to develop as one of the tourism product for Islamic tourism. Therefore, the Islamic building and architecture can be one of the products to market and promote in order to increase and attract the tourists from domestic and international to visit Islamic architecture in Malaysia specifically in Terengganu. However, the statistics in 2018 by Department of Statistics Malaysia about domestic tourism survey was recorded that, Islamic architecture is very less popular among tourists as the purposes of visiting. Due to this, it can be seen lack of awareness about the development and the potential of Islamic architecture as one of the tourism product. Hence, this study aims to discover the most influential experience factor of Islamic architecture and to investigate the experience factor can influence Islamic architecture in Kuala Terengganu focusing on three factors which are Islamic attributes, destination image and service quality. The research design applied in this study is a quantitative approach in which questionnaire as the instrument and the targeted respondents is any tourists who had experienced in visiting Islamic architecture in Kuala Terengganu. The result of this study demonstrates that the destination image is the most influential experience factor of the destination loyalty in visiting Islamic architecture. In short, it will be significantly useful to know the experience factor that influenced tourists’ destination loyalty towards visiting Islamic architecture experience in Kuala Terengganu.